(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
This work aims, from a perspective placed at the crossing between cultural and gender studies, to contribute to the analysis of the testimonial narratives published during the 1970s in the rioplatense field which recover women’s militancy experiences. With this objective, a corpus comprising testimonial narrations produced during the 1968- 1976 period by Argentinean writers and columnists Rodolfo Walsh and Francisco Urondo, and by the Uruguayan columnist María Esther Giglio is approached. This research tries to analyze these women’s militancy experiences as a complex dimension located in the tension between past and present, individual and collective, and liked to the material conditions in which that lived experiences is thought, represented and put on the order of language.